Effects of Ethinylestradiol (EE2) and an Organophosphorus Flame Retardant (TCPP) on Gonadal Maturation in the Sea Urchin, Paracentrotus lividus - Pedro Campoy-López; Estefanía Pereira-Pinto; Leonardo Mantilla-Aldana; Ricardo Beiras (Journal of Marine Science and Engineering, 2020)
The sea urchin (Paracentrotus lividus) was used to test the effects of one of the most abundant flame retardant additives for plastics, tris (1-chloro-2-propyl) phosphate (TCPP), and the synthetic hormone ethinylestradiol (EE2) on gametogenesis and gonad development of adults. With this aim, 403 individuals of both sexes were exposed to TCPP concentrations ranging from 0.2 to 10 µg/L, EE2 (0.01 µg/L), seawater and solvent controls for 7 and 28 days. EE2 and TCPP exposure did not cause histological damage in the gonads. Some evidence of estrogenic effects of TCPP within the µg/L range and EE2 within the ng/L range is reported. Females exposed to 1 µg/L TCPP for 7 days showed a significant increase in gonad development assessed as gametogenic stage, females exposed to 10 µg/L TCPP showed increased gonad development both in terms of weight (Gonad Index, GI, at both 7 and 28 days) and maturation (Pixelar Index, PI), and females exposed to 10 ng/L EE2 showed increased PI after 28 days exposure. Male sea urchins exposed to both TCPP and EE2 for 7 days showed increased frequencies of low development gonad stage. However, the patterns of response are affected by the high inter-individual variability, the differing initial stage of the gonad, as well as the dosage administered.